Gender specific considerations in septorhinoplasty, a retrospective observational study and review of the literature. (June 2022) - Gillanders, S.L.; Walsh, M.; Anderson, S.; Abdulrahman, S.
Abstract: Introduction: In our service experience, we found we had a high proportion of male patients undergoing septorhinoplasty. This encouraged us to research gender specific differences in anatomy, surgical techniques, expectations and outcomes. Methods: We performed a retrospective chart review of patients who have had rhinoplasty surgery under a single otolaryngology consultant with a special interest in rhinoplasty. Patient information and results of the 10-Item Standardized Cosmesis and Health Nasal Outcomes Survey for Functional and Cosmetic Rhinoplasty pre and post-surgery were collected. Results: There was no statistically significant difference in the mean pre-operative symptom (29.31 vs 32.29 p = 0.559), change in symptom (23.25 vs 24.14 p = 0.827) or satisfaction scores (8.69 vs 7.29 p = 0.089) between male and female patients. A discussion on gender specific anatomical features and deformities is presented. Conclusion: All patients reported improved symptoms and high levels of satisfaction. Careful patient counselling and patient-specific surgical planning help to achieve optimal outcomes. Highlights: Traumatic nasal bone injury is a common cause of cosmetic and functional issues seen in the Otolaryngology outpatients. Limited research exists on male rhinoplasty despite its growing popularity. Knowledge of individual anatomical variations and surgical technique is key to providing personalised patient care. Careful patient counselling and patient specific surgical planning help to achieve optimal outcomes.